Environmental Enrichment Induces Changes in Long-Term Memory for Social Transmission of Food Preference in Aged Mice through a Mechanism Associated with Epigenetic Processes - Simona Cintoli; Maria Cristina Cenni; Bruno Pinto; Silvia Morea; Alessandro Sale; Lamberto Maffei; Nicoletta Berardi (Neural Plasticity)
Decline in declarative learning and memory performance is a typical feature of normal aging processes. Exposure of aged animals to an enriched environment (EE) counteracts this decline, an effect correlated with reduction of age-related changes in hippocampal dendritic branching, spine density, neurogenesis, gliogenesis, and neural plasticity, including its epigenetic underpinnings. Declarative memories depend on the medial temporal lobe system, including the hippocampus, for their formation, but, over days to weeks, they become increasingly dependent on other brain regions such as the neocortex and in particular the prefrontal cortex (PFC), a process known as system consolidation. Recently, it has been shown that early tagging of cortical networks is a crucial neurobiological process for remote memory formation and that this tagging involves epigenetic mechanisms in the recipient orbitofrontal (OFC) areas. Whether EE can enhance system consolidation in aged animals has not been tested; in particular, whether the early tagging mechanisms in OFC areas are deficient in aged animals and whether EE can ameliorate them is not known. This study aimed at testing whether EE could affect system consolidation in aged mice using the social transmission of food preference paradigm, which involves an ethologically based form of associative olfactory memory. We found that only EE mice successfully performed the remote memory recall task, showed neuronal activation in OFC, assessed with c-fos immunohistochemistry and early tagging of OFC, assessed with histone H3 acetylation, suggesting a defective system consolidation and early OFC tagging in aged mice which are ameliorated by EE.